2019
DOI: 10.3389/fphys.2019.00057
|View full text |Cite
|
Sign up to set email alerts
|

Altered Venous Blood Nitric Oxide Levels at Depth and Related Bubble Formation During Scuba Diving

Abstract: Introduction: Nitric oxide (NO) plays an important role in the physiology and pathophysiology of diving, and the related endothelial dysfunction and oxidative stress roles have been extensively investigated. However, most available data have been obtained before and after the dive, whilst, as far as we know, no data is available about what happens during the water immersion phase of dive. The scope of this study is to investigate the Nitrate and Nitrite (NO X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Bubbles in turn could also activate hemostatic pathways and induce increases in circulating MPs, which could further impair arterial endothelial function (Lambrechts et al 2017). Also, diving-related changes in NO could activate processes like platelet activation, leukocyte adhesion, and thrombosis (Cialoni et al 2019). Bubble-induced MPs may only occupy a section of all MPs after DCS.…”
Section: Discussionmentioning
confidence: 99%
“…Bubbles in turn could also activate hemostatic pathways and induce increases in circulating MPs, which could further impair arterial endothelial function (Lambrechts et al 2017). Also, diving-related changes in NO could activate processes like platelet activation, leukocyte adhesion, and thrombosis (Cialoni et al 2019). Bubble-induced MPs may only occupy a section of all MPs after DCS.…”
Section: Discussionmentioning
confidence: 99%
“…Before the analysis 400 μl of each plasma sample were treated with 400 μl of acetonitrile to precipitate proteins ( Romitelli et al, 2007 ). Briefly, we used a method based on Griess’s reaction as an index of NO concentration ( Green et al, 1982 ), according to Cialoni et al (2019) . Plasma NOx levels were obtained by interpolation of NaNO3 standard ( Tsikas, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…NO plays a pivotal role also in subjects exposed to high hydrostatic pressures ( Theunissen et al, 2013a ), and recent measurements taken in scuba divers at −40 m depth showed remarkable increases in the plasma concentrations of NO derivatives ( Cialoni et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, 400 µl of the sample was treated with 400 µl of acetonitrile (Romitelli et al, 2007) to precipitate the proteins and centrifuged at 12,000 rpm for 10 min. NOx was measured in the deproteinized plasma using a method based on Griess's reaction as an index of NO concentration (Green et al, 1982), according to Cialoni et al (2019). Plasma NOx levels were obtained by interpolation of standard NaNO 3 curves (Tsikas, 2005).…”
Section: Plasma Nox Measurementmentioning
confidence: 99%